Pengelolaan Life Skill Di SMK Negeri 1 Purworejo - Yanwati, Heni; Sutama, Sutama (2017)
This study aims to: 1) describe the Life Skills lesson planning in SMK Negeri 1 Purworejo, 2) describe the management of teaching materials teaching Life Skills in SMK Negeri 1 Purworejo, 3) describe the Life Skills learning interactions in SMK Negeri 1 Purworejo. This study used a qualitative research with the main subject of this research is the principal, and teachers of SMK Negeri 1 Purworejo. Data collection techniques used in this research is the direct observation, interviews and document analysis. Data analysis techniques in this study using a model of analysis, data collection, data reduction, data presentation, and conclusion. The validity of the data in this study include credibility (internal validity), transferability (external validity), dependability (reliability), and confermability(objectivity). The results of the study provide an overview: 1) the learning plan Life Skill at SMK Negeri 1 Purworejo: curriculum by synchronizing business "Krypton Gama Jaya", the use of the apprenticeship system 2) describe the management of teaching materials Life Skill at SMK Negeri 1 Purworejo: arranged on Spectrum Expertise SMK, SMK Negeri 1 Purworejo take expertise: Technology and Engineering, Program expertise: 1.6 Mechanical Machining and expertise Package: 1.6.1 Mechanical Machining with Code Number: 013, the material consists of 30% theory and 70% practical, vocational subjects consists of basic vocational, basic competence vocational and vocational competence 3) learning interactions Life Skills in SMK Negeri 1 Purworejo: designed to provide a learning experience that involves mentally and physically through interaction between learners, learners with the teacher, the environment, and resources learn more in order to achieve basic competence, competency standards, competency standards subjects